2016
DOI: 10.1021/acs.jctc.6b01053
|View full text |Cite
|
Sign up to set email alerts
|

An EOM-CCSD-PCM Benchmark for Electronic Excitation Energies of Solvated Molecules

Abstract: In this work, we benchmark the equation of motion coupled cluster with single and double excitations (EOM-CCSD) method combined with the polarizable continuum model (PCM) for the calculation of electronic excitation energies of solvated molecules. EOM-CCSD is one of the most accurate methods for computing one-electron excitation energies, and accounting for the solvent effect on this property is a key challenge. PCM is one of the most widely employed solvation models due to its adaptability to virtually any so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 72 publications
(104 reference statements)
1
58
0
Order By: Relevance
“…In fact, we showed that significant and consistent corrections to the CCSD-PCM results can be readily obtained (at DFT level) by adding a few explicit solvent molecules hydrogen-bonded to the solute, and surrounding the whole cluster in the continuum solvent. [21] With this mixed implicit/explicit model, the transition energy shifts to lower values compared to a PCM-only calculation, as shown in Figure 6. In our experience, it is important to saturate the H-bond sites with explicit solvent molecules, and the external PCM cavity should include added spheres to avoid unphysical solvent pockets in the crevices of the cavity.…”
Section: Figurementioning
confidence: 90%
See 4 more Smart Citations
“…In fact, we showed that significant and consistent corrections to the CCSD-PCM results can be readily obtained (at DFT level) by adding a few explicit solvent molecules hydrogen-bonded to the solute, and surrounding the whole cluster in the continuum solvent. [21] With this mixed implicit/explicit model, the transition energy shifts to lower values compared to a PCM-only calculation, as shown in Figure 6. In our experience, it is important to saturate the H-bond sites with explicit solvent molecules, and the external PCM cavity should include added spheres to avoid unphysical solvent pockets in the crevices of the cavity.…”
Section: Figurementioning
confidence: 90%
“…The figure reports data for both nonequilibrium and equilibrium solvation regimes; the errors are considerably larger in the equilibrium solvation regime because the full dielectric constant ε 0 is used to evaluate the excited state solvent response. The cLR approach is able to reproduce the PTED results very well, and it can be used for initial studies of excited state ordering before searching for excited The main comparison with experimental transition energies is based on a benchmark study we conducted recently, [21] where we selected 16 small to medium size molecules where measurements were available in polar solvents, shown in Figure 4. [67][68][69][70][71] The measured transition energies were used as reference for CCSD, three global hybrid functionals: B3LYP, [72] PBE0, [73,74] and M06, [75] and two range-separated hybrid functionals: CAM-B3LYP [76] and LC-ωPBE.…”
Section: Representative Applicationsmentioning
confidence: 99%
See 3 more Smart Citations